Level of pandemic consequences for the indebtedness of the Slovak hospitality sector - Katarina Valaskova; Pavol Durana; Tomas Kliestik; Simona Vojtekova (Investment Management & Financial Innovations)
The financial impact of the COVID-19 pandemic on entire economies has been proven. The current necessity is to determine the level of consequences for distinct industries and sectors. The local lockdowns and travel restrictions shocked the hospitality industry and its performance. Thus, the purpose of this study is to explain the effect of the pandemic on a particular economic sector, specifically NACE I (Accommodation and food service activities), and changes in financial indicators in Slovak circumstances for the period 2016–2021. The study focuses on debt ratios that reflect the financial stability of businesses. Friedman’s test was run to determine how the chosen indebtedness indicators developed over the chosen years. Based on a sample of 321 Slovak companies, statistically significant differences were found. But only the interest coverage ratio was significantly different between the pre-pandemic and pandemic eras, according to the post-hoc tests. In addition, there was a hint of a positive overall transformation in the sector of accommodation and food service activities. The decline of the number of enterprises by total indebtedness from the alarming threshold in 2021 declared this fact. The conclusions implicate that Slovak businesses are becoming more mindful of debt financing and are attempting to reduce the risks of going bankrupt. AcknowledgmentThis research was financially supported by the Slovak Research and Development Agency – Grant Vega 1/0121/20: Research of transfer pricing system as a tool to measure the performance of national and multinational companies in the context of earnings management in conditions of the Slovak Republic and V4 countries and faculty institutional research 1/KE/2022: Analysis of the determinants of indebtedness and profitability of business entities in the European area.